(untitled) (Architecture Image Studies, 2026)
Space resource management is a critical determinant of teaching and learning efficiency, especially in design-focused disciplines like architecture, where the physical environment directly impacts creativity and collaborative outcomes. This research investigates the escalating challenge of space scarcity at the Faculty of Architecture, Khon Kaen University, a constraint that undermines its capacity to accommodate diverse modern teaching methods and the rapid growth in student enrollment.This study employs a qualitative case study methodology, involving a comprehensive survey of instructional spaces and an analysis of usage patterns to develop a utilization plan for both formal and informal learning areas. The primary outcomes include a diagnostic problem assessment and a strategic framework outlining approaches for adaptive reuse, space reconfiguration, and optimizing the use of existing architectural infrastructure.Key findings confirm the necessity of transitioning from fixed-function spaces to flexible, multi-modal environments. Strategic recommendations include implementing "Super rooms," transforming traditional computer labs into flexible learning spaces, and upgrading open or transitional areas (such as under-building spaces, corridors, and halls) into small, multi-purpose, or informal learning zones. The study concludes that sustainable spatial flexibility can be achieved through innovative physical management and design thinking processes, offering a more viable and scalable alternative to costly building expansion or new construction within the context of resource-limited educational institutions.